SISTEM PAKAR BERBASIS WEB UNTUK MENENTUKAN UNSUR – UNSUR KIMIA GOLONGAN A BERDASARKAN KARAKTERISTIKNYA - Rudi Zakaria; Nanan Rohman (STMIK Mardira Indonesia, Bandung, 2015)
Following the increasing of human cultured and the developing of technology without the awareness computer has it’s big function in the world technology research and industry. Especially in it’s function as an equipment to input and data prosessing. Software expert system to decide the A group of chemist element based on characterism, from computer science and mathematics turn up lots of programmes which made all the calculation and the function become easier and useful. The software had been used to definite the A group of chemist element without identification by anyone or eventhough by a chemist analyst, it can’t be identify or decided the name of chemist element. This software is also on purpose to help the students (university students) in learning chemist science proses or about the developing of chemist science recently. In combine the software web base expert system to decide the A group of chemist element depend on its own characterism, the writer using the metode which object oriented. The software was built by using PHP version 5.3 and database My SQL language programming. Keyword : elements of Chemistry, mathematics, Software Web-based Expert System AbstrakSetelah peningkatan berbudaya manusia dan pengembangan teknologi tanpa komputer kesadaran memiliki itu fungsi besar dalam penelitian teknologi dunia dan industri. Terutama di dalamnya berfungsi sebagai alat input dan data prosessing. Software sistem pakar untuk menentukan kelompok A unsur kimia berdasarkan karakteristik dari ilmu komputer dan matematika muncul banyak program yang membuat semua perhitungan dan fungsi menjadi lebih mudah dan berguna. Perangkat lunak ini telah digunakan untuk pasti kelompok A unsur kimia tanpa identifikasi oleh siapapun atau walaupun oleh seorang analis kimia, tidak dapat mengidentifikasi atau memutuskan nama elemen kimia . Perangkat lunak ini juga bertujuan untuk membantu siswa (mahasiswa) dalam belajar ilmu kimia atau Proses tentang pengembangan ilmu kimia baru-baru ini. Dalam menggabungkan sistem perangkat lunak pakar berbasis web untuk menentukan kelompok A unsur kimia tergantung pada karakteristik itu sendiri, penulis menggunakan metoda analisis yang berorientasi objek. Perangkat lunak ini dibangun dengan menggunakan PHP versi 5.3 dan database yang saya bahasa pemrograman SQL. Kata Kunci: Elements Of Chemistry, Mathematics, Software Web-Based Expert System